Evaluation Of The Health Care System For People With Mental Health Disorder At The Panjang Inpatient Health Center Bandar Lampung City - Mike Yulia Fandri; Lolita Sary; Fitri Ekasari (Malahayati Nursing Journal, 2022)
ABSTRACTMental health is an important aspect in realizing public health as a whole. Currently, the estimated number of people with mental disorders in the world is around 450 million people, including schizophrenia. The performance of the Regency/City Government in mental health services for people with mental disorders according to the standards in the work area is 100 percent. Based on data from the Bandar Lampung City Health Office, the achievement of minimum service standard (MSS) in mental health services sufferers in 2019 from 31 Puskesmas found that there were 21 Puskesmas with MSS achievements not reaching 100%. Data on the achievements of MSS with 100% and services in accordance with existing targets in the work area are found at the Gedong Air Health Center, and Sukaraja Health Center. The health center with more achievements compared to the target at the Kedaton Health Center 113.33%. Puskesmas with low achievement are Puskesmas Panjang SPM 40.44%. The number of mental health disorder patients visiting the Puskesmas decreased from the previous year, the number of patient visits in 2018 was 408, in 2019 it was 262, and in 2020 it was 187 patients. The purpose of this study is to evaluate the health care system for people with mental health disorders at the Panjang Inpatient Health Center in 2021 starting from the input, process and output. This research is a qualitative research with a case study approach, the technique of determining participants is using purposive sampling. The research was conducted at the Panjang Inpatient Health Center in August-September 2021. The research informants consisted of 5 informants consisting of the Head of the health centre, doctors, nurses, and families of patients. Data collection techniques using interviews and observation. The results showed that the inputs including the budget for the program came from the health operational assistance fund, but the funds for the fulfillment of the facilities and infrastructure for the program were not sufficient. Implementing personnel are still lacking and have not received training, facilities and infrastructure do not have a mental health clinic and there is no mental medicine available. The process, including the activities of the program, has not been running well so that the output produced by the number of visits and the coverage of the mental health disorder service MSS has not reached the target. Based on the research results, it can be concluded that the health services for patient at the Panjang Inpatient Health Center have not been maximized, so it is hoped that the Bandar Lampung City Health Office will increase supervision, guidance and provide mental health training for health workers. Hoped there will be a proactive attitude to reach the community throughout its working area, complete the facilities and infrastructure.Keywords: Evaluation, Health Care System, Mental Health DisorderABSTRAKKesehatan jiwa merupakan aspek penting dalam mewujudkan kesehatan masyarakat secara menyeluruh. Saat ini perkiraan jumlah penderita gangguan jiwa di dunia adalah sekitar 450 juta jiwa termasuk skizofrenia. Capaian kinerja Pemerintah Daerah Kabupaten/Kota dalam pelayanan kesehatan jiwa pada orang dengan gangguan jiwa berat sesuai standar di wilayah kerja adalah 100%.  Berdasarkan data dari Dinas Kesehatan Kota Bandar lampung, data capaian Standar Pelayanan Minimal (SPM) Orang Dengan Gangguan Jiwa (ODGJ) tahun 2019 dari 31 Puskesmas didapatkan bahwa terdapat 21 Puskesmas dengan capaian SPM belum mencapai 100%. Data capaian SPM 100% dan pelayanan sesuai dengan sasaran yang ada diwilayah kerja terdapat pada Puskesmas Gedong Air dan Puskesmas Sukaraja. Puskesmas dengan capaian lebih banyak di bandingkan dengan sasaran yaitu Puskesmas Kedaton SPM 113,33%. Puskesmas dengan capaian rendah yaitu Puskesmas Panjang SPM 40,44%. Jumlah pasien ODGJ yang berkunjung ke Puskemas menurun dari tahun sebelumnya, angka kunjungan pasien ODGJ tahun 2018 sebesar 408, tahun 2019 sebesar 262, dan tahun 2020 sebesar 187 pasien. Tujuan penelitian ini adalah evaluasi sistem pelayanan kesehatan orang dengan gangguan jiwa (ODGJ) di Puskesmas Rawat Inap Panjang Tahun 2021 mulai dari input, proses dan output. Penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus, teknik penentuan partisipan menggunakan purposive sampling. Penelitian dilakukan di Puskesmas Rawat Inap Panjang pada bulan Agustus - September 2021. Informan penelitian sebanyak 5 informan terdiri dari Kepala Puskesmas, dokter, perawat, dan keluarga pasien ODGJ. Teknik pengumpulan data menggunakan wawancara dan observasi. Hasil penelitian menunjukkan bahwa input meliputi anggaran program ODGJ berasal dari dana bantuan operasional kesehatan (BOK), namun dana untuk pemenuhan sarana dan prasarana program ODGJ belum mencukupi. Tenaga pelaksana masih kurang dan belum mendapat pelatihan, sarana dan prasarana belum memiliki poli jiwa dan tidak tersedia obat jiwa. Proses meliputi kegiatan program ODGJ belum berjalan dengan baik sehingga output yang dihasilkan angka kunjungan dan cakupan SPM pelayanan ODGJ belum mencapai target. Berdasarakan hasil penelitian dapat disimpulkan bahwa pelayanan kesehatan ODGJ di Puskesmas Rawat Inap Panjang belum maksimal, maka diharapkan kepada Dinas Kesehatan Kota Bandar Lampung meningkatkan pengawasan, pembinaan serta memberikan pelatihan kesehatan jiwa bagi tenaga kesehatan. Diharapkan adanya sikap proaktif untuk menjangkau masyarakat di seluruh wilayah kerjanya, melengkapi sarana dan prasarana.Kata kunci: Evaluasi, Sistem Pelayanan Kesehatan, ODGJ